Populism, Constitution Making, and the Rule of Law in Latin America - Carlos de la Torre; Felipe Burbano de Lara (Partecipazione e Conflitto, 2020)
The article explores the effects of populist polarization in creating strong and long-lasting institutions based on the rule of law. It focuses on politics and not on the political economy of populism or of natural resource extraction. The first section briefly explains how we understand the contested notions of populism and the rule of law. The second focuses on the paradigmatic case of Juan Perón's first two administrations (1946-1956) to explore the ambiguous legacies of populist inclusion for the creation of long-lasting demo-cratic institutions. The third section focuses on how Hugo Chávez, Evo Morales and Rafael Correa appealed to the un-bounded will of the people to convene participatory constituent assemblies. The last section focuses on Ecuador's post-populist succession. Different from Evo Morales that was ousted by a coup, or Nicolás Maduro that killed democracy, Lenín Moreno, who was Correa's former vice-president, abandoned populism, ditched his mentor, and used a referendum to clean the state and political institutions from Correa's allies. Appealing to the people directly, his administration assumed exceptional powers to name new authorities of control and accountability. His institutional reforms however might not last because they were based on the exclusion of Correa and his followers. The conclusion explores the reasons why actors continue to use laws instrumentally making it difficult to create long-lasting institutional arrangements based on the rule of law, and hence on the possibility of deepening democracy.